Serum concentrations of beta-hexachlorocyclohexane in groups of the Italian general population: a human biomonitoring study - Anna Maria Ingelido; Annalisa Abballe; Valentina Marra; Silvia Valentini; Annamaria Ferro; Maria Grazia Porpora; Pietro Gino Barbieri; Elena De Felip (Istituto Superiore di Sanità, 2009)
Because of its persistence and toxicological profile, beta-hexachlorocyclohexane (β-HCH) has been proposed for inclusion in the Stockholm Convention on persistent organic pollutants (POPs). Although the use of technical HCH, which is the primary source of β-HCH in the environment, has been banned in the EU in 1978 and progressively at a global level, β-HCH is still detectable in the general environment worldwide. Human exposure mostly occurs via food and may be of concern in areas where illegal use and/or improper disposal of stockpiles occurred and locally grown food is consumed. Exposure of the Italian general population to β-HCH has been poorly characterised. Lack of human biomonitoring data severely hinders the ability to interpret potential increases in exposure related to situations of environmental risk. We carried out a human biomonitoring study aimed to provide baseline information on background exposure of the Italian general population to this pollutant. For this purpose, we analysed 116 serum samples from groups of subjects of both sex from the general population residing in three Italian towns at different latitudes. Serum concentrations of β-HCH resulted to be comprised between 1.64 and 300 ng/g fat, with a median value of 18.0 ng/g fat and a 90th percentile of 65.9 ng/g fat. The serum concentrations detected are in line with those detected in most Western European countries.